Electrophotographic photoreceptor, process cartridge, and image forming apparatus

By incorporating an undercoat layer with specific electron transporting materials and structural characteristics in the electrophotographic photoreceptor, the electron transport properties and electrostatic maintenance are significantly improved.

JP2025052781APending Publication Date: 2025-04-07FUJIFILM BUSINESS INNOVATION CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023161677
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Conventional electrophotographic photoreceptors have limitations in electron transport properties, leading to reduced electrostatic maintenance.

Method used

The electrophotographic photoreceptor is designed with an undercoat layer containing a binder resin and an electron transporting material, where the full width at half maximum (FWHM) of the maximum intensity peak in the X-ray diffraction spectrum is 5.0° or less, and the crystal density of the electron transporting material is 1.62g/cm³, optimizing electron transport properties.

Benefits of technology

This configuration enhances electron transport properties, resulting in improved electrostatic maintenance and superior performance compared to conventional photoreceptors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025052781000001_ABST
    Figure 2025052781000001_ABST
Patent Text Reader

Abstract

To provide an electrophotographic photoreceptor that is excellent in electron transport property.SOLUTION: An electrophotographic photoreceptor comprises a conductive substrate, an undercoat layer provided on the conductive substrate, and a photosensitive layer provided on the undercoat layer. The undercoat layer contains a binder resin, and an electron transport material having a crystal density of 1.62 g / cm3 or more. In the undercoat layer, the full width at half maximum (FWHM) of the maximum intensity peak in an X-ray diffraction spectrum measured from a thickness direction, is 5.0° or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrophotographic photoreceptor, a process cartridge, and an image forming apparatus. [Background technology]

[0002] In an electrophotographic image forming apparatus, generally, the surface of an electrophotographic photoreceptor is charged to a predetermined polarity and potential by a charging means, and the surface of the electrophotographic photoreceptor after charging is selectively discharged by image exposure to form an electrostatic latent image, and then a developing means attaches toner to the electrostatic latent image, developing the latent image into a toner image. Then, the toner image is transferred to a transfer medium by a transfer means, and the image formed is discharged. In recent years, electrophotographic photoreceptors have the advantages of high speed and high print quality, and are therefore widely used in fields such as copying machines and laser beam printers.

[0003] Currently, in many cases, electrophotographic photoreceptors are produced by forming an undercoat layer on a conductive support layer such as an aluminum base material, and then forming a photosensitive layer on the undercoat layer.

[0004] The undercoat layer is required to suppress charge injection into the photosensitive layer when a voltage is applied to the electrophotographic photoreceptor while concealing defects in the substrate, and to control the resistance. On the other hand, the undercoat layer is also required to suppress the charge generated in the photosensitive layer from being retained inside the photoreceptor, that is, to have charge transportability.

[0005] Patent Document 1 discloses an electrophotographic photoreceptor having an undercoat layer and a photosensitive layer provided in this order on a conductive support, the undercoat layer containing dichlorotin phthalocyanine and a binder resin.

[0006] Patent Document 2 discloses an electrophotographic photoreceptor in which an undercoat layer, a charge generating layer, and a charge transport layer are sequentially laminated on a conductive layer, and the undercoat layer contains a binder, an organic charge generating material, and a specific diphenoquinone derivative.

[0007] Patent Document 3 discloses an electrophotographic photoreceptor characterized in that it comprises a photosensitive layer containing a charge generating agent provided on a conductive support, the charge generating agent being obtained by sublimation purification of a specific benzimidazole perylene pigment and dry pulverization, and that in X-ray diffraction measurement of the powder in a non-oriented state using CuKα radiation as a light source, the electrophotographic photoreceptor has a crystal form with Bragg angles (2θ±0.2°) of 2θ=6.2°, 12.3°, and 26.8°, and the half-value width at 26.8°, S(26.8°), is S(26.8°)≧0.5.

[0008] Patent Document 4 discloses an electrophotographic photoreceptor in which an undercoat layer and a photosensitive layer are sequentially laminated on a conductive support, the undercoat layer being characterized in that it contains an organic pigment and a rosin compound in a polyamide resin. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 11-202520 [Patent Document 2] Japanese Patent Application Publication No. 03-216662 [Patent Document 3] Japanese Patent Application Publication No. 05-249719 [Patent Document 4] Japanese Patent Application Publication No. 11-184129 Summary of the Invention [Problem to be solved by the invention]

[0010] In a conventional electrophotographic photoreceptor including a conductive substrate, an undercoat layer and a photosensitive layer, improving the electron transporting property tends to result in a decrease in the charge retaining property. In the present disclosure, when the full width at half maximum (FWHM) of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer containing a binder resin and an electron transporting material exceeds 5.0°, or the crystal density of the electron transporting material is 1.62 g / cm 3It is an object of the present invention to provide an electrophotographic photoreceptor having excellent electron transport properties as compared with a case where the electron transport properties are less than 100%. [Means for solving the problem]

[0011] Specific means for solving the above problems include the following aspects.

[0012] <1> A conductive substrate; an undercoat layer provided on the conductive substrate; a photosensitive layer provided on the undercoat layer; Equipped with The undercoat layer is made of a binder resin and a crystal density of 1.62 g / cm 3 and wherein the full width at half maximum (FWHM) of the maximum intensity peak in an X-ray diffraction spectrum measured in the thickness direction is 5.0° or less. <2> The electron transporting material has an aspect ratio of 1.0 or more and 2.5 or less. <1> The electrophotographic photoreceptor according to claim 1. <3> The electron transporting material has an aspect ratio of 1.5 or more and 2.3 or less. <2> The electrophotographic photoreceptor according to claim 1. <4> The relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer is I 1 year, The above undercoat layer is powdered with a volume average particle size of 5 μm or less and the relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum is measured. 2 where N is the maximum value of the orientation index N represented by the following formula (1), Nmax is 1.0 or more and 5.5 or less. <1> The electrophotographic photoreceptor according to claim 1.

number

[0013] <1> According to the invention, when the full width at half maximum (FWHM) of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer containing a binder resin and an electron transporting material exceeds 5.0°, or the crystal density of the electron transporting material is 1.62 g / cm 3 In comparison with the case where the content is less than 100%, an electrophotographic photoreceptor having excellent electron transport properties is provided. <2> According to the present invention, an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case where the aspect ratio of the electron transport material exceeds 2.5. <3> According to the present invention, an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with the case where the aspect ratio of the electron transport material is less than 1.5 or exceeds 2.3. <4> According to the present invention, the relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer is I 1 The relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured by powdering the undercoat layer with a volume average particle size of 5 μm or less was defined as I 2In this case, an electrophotographic photoreceptor having excellent electron transport properties can be provided, as compared with a case in which the maximum value Nmax of the orientation index N represented by the formula (1) is 1.0 or more and exceeds 5.5. <5> According to the present invention, an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case in which the LUMO energy level of the undercoat layer is less than 3.8 eV or more than 4.2 eV.

[0014] <6> , <7> or <8> According to the invention related to the above, an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with the case where the electron transport material contains the following compound (D) or compound (E). [ka]

[0015] <9> According to the present invention, an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case in which the average primary particle diameter of the electron transport material exceeds 500 nm. <10> According to the present invention, an electrophotographic photoreceptor having excellent electron transport properties is provided, compared to when the content of the electron transport material is less than 60 mass % or more than 75 mass % with respect to the total binder resin content of the undercoat layer. <11> According to the present invention, an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with the case where the thickness of the undercoat layer is less than 5 μm or exceeds 15 μm. <12> According to the present invention, an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case in which the proportion of the metal oxide in the undercoat layer exceeds 5 mass % with respect to the total solid content of the undercoat layer. <13> or <14> According to the invention, in the case of an electrophotographic photoreceptor having an X-ray diffraction spectrum of a maximum intensity peak having a full width at half maximum (FWHM) of more than 5.0° as measured in the thickness direction of an undercoat layer containing a binder resin and an electron transporting material, or in the case of an electrophotographic photoreceptor having a crystal density of 1.62 g / cm 3 In comparison with a process cartridge or image forming apparatus having an electrophotographic photosensitive member with an excellent electron transporting property, a process cartridge or image forming apparatus having an electrophotographic photosensitive member with an excellent electron transporting property is provided. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a schematic partial cross-sectional view showing an example of a layer structure of the electrophotographic photoreceptor according to the present embodiment. [Diagram 2] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 3] FIG. 4 is a schematic configuration diagram illustrating another example of an image forming apparatus according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0018] In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0019] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified. In this disclosure, LUMO is an abbreviation for "Lowest Unoccupied Molecular Orbital."

[0020] In this disclosure, the electrophotographic photoreceptor is also simply referred to as a photoreceptor.

[0021] <Electrophotographic photoreceptor> The electrophotographic photoreceptor according to the present embodiment includes a conductive substrate, an undercoat layer provided on the conductive substrate, and a photosensitive layer provided on the undercoat layer. The undercoat layer contains a binder resin and a photosensitive layer having a crystal density of 1.62 g / cm. 3 or more, and the full width at half maximum (FWHM) of the maximum intensity peak in an X-ray diffraction spectrum measured in the thickness direction is 5.0° or less.

[0022] The photoreceptor according to this embodiment includes a conductive substrate, an undercoat layer disposed on the conductive substrate, and a photosensitive layer disposed on the undercoat layer. Fig. 1 shows a schematic example of a layer structure of a photoreceptor according to this embodiment. Photoreceptor 7A shown in Fig. 1 has a structure in which an undercoat layer 1, a charge generation layer 2, and a charge transport layer 3 are laminated in this order on a conductive substrate 4. The charge generation layer 2 and the charge transport layer 3 constitute a photosensitive layer 5. Photoreceptor 7A may have a layer structure in which a protective layer is further provided on the charge transport layer 3.

[0023] In the photoreceptor according to this embodiment, the photosensitive layer may be a functionally separated type photosensitive layer in which a charge generation layer 2 and a charge transport layer 3 are separated, as in the photoreceptor 7A shown in FIG. 1, or may be a single-layer type photosensitive layer having a charge generation function and a charge transport function, instead of the charge generation layer 2 and the charge transport layer 3.

[0024] In order to improve the electron transporting property of an electrophotographic photoreceptor, an electrophotographic photoreceptor having an undercoat layer is used. However, there is room for improvement in the electron transporting performance of a conventional electrophotographic photoreceptor having an undercoat layer.

[0025] On the other hand, the electrophotographic photoreceptor according to the present embodiment has the above-mentioned structure, and therefore has excellent electron transport properties. The mechanism of this action is not necessarily clear, but is presumed to be as follows. The undercoat layer in the electrophotographic photoreceptor according to this embodiment has a crystal density of 1.62 g / cm 3The electron transporting material contains the above-mentioned. In other words, the crystal density of the electron transporting material is relatively high compared to conventional materials. The crystal density usually indicates the molecular weight in a unit cell / the volume of a crystal unit cell. Because the crystal density is relatively high, the electron transporting materials tend to be present close to each other in the undercoat layer. As a result, the overlap of the LUMO energy levels of the electron transporting materials is likely to be large, and it is considered that the electron transporting property is excellent. In addition, the undercoat layer in the electrophotographic photoreceptor according to the present embodiment has a full width at half maximum (FWHM) of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of 5.0° or less. In general, the peak in the X-ray diffraction spectrum tends to be observed sharper when the purity is high and the distortion of the crystal lattice is small, without impurities or types of crystals being mixed. In other words, when the full width at half maximum (FWHM) of the maximum intensity peak is 5.0° or less, there is little mixing of multiple types of crystals, and the arrangement of the electron transporting materials in the undercoat layer tends not to be disordered. As a result, it is considered that the electron transporting property is further improved.

[0026] Each layer of the photoreceptor according to this embodiment will be described in detail below.

[0027] [Sublayer] The undercoat layer is made of a binder resin and has a crystal density of 1.62 g / cm 3 or more, and the full width at half maximum (FWHM) of the maximum intensity peak in an X-ray diffraction spectrum measured in the thickness direction is 5.0° or less.

[0028] (electron transport material) The electron transport material has a crystal density of 1.62 g / cm 3 More than 1.64g / cm 3 More than 3.00g / cm 3 It is preferable that the density is 1.66 g / cm or less. 3 More than 2.50g / cm 3 More preferably, it is 1.68 g / cm or less. 3 More than 1.90g / cm 3 It is even more preferable that: The crystal density of the electron transport material is 1.62 g / cm 3 That is, when the crystal density is relatively high, the molecules tend to be close to each other in the crystal structure, which leads to a large overlap of the LUMO energy levels of the electron transporting materials, resulting in superior electron transport properties. The crystal density of the electron transport material is 3.00 g / cm 3 If the molecular weight is less than this, the molecules in the crystal structure are prevented from being too closely spaced from each other, which is believed to result in more stable crystal structure because the energy repulsion between the molecules is more easily suppressed.

[0029] The crystal density of the electron transporting material is determined as follows. The layer on the outer periphery side of the undercoat layer in the electrophotographic photoreceptor, i.e., the photosensitive layer, is removed using a solvent to leave only the conductive substrate and the undercoat layer. Then, after peeling off the undercoat layer from the conductive substrate, the volume average particle size of the electron transport material contained in the undercoat layer is adjusted to 5 μm or less, and X-ray diffraction measurement (XRD measurement) is performed. The obtained X-ray diffraction profile is compared with a database (e.g., Cambridge Structural Database: CSD, Crystallography Open Database: COD, etc.), and a compound with a matching X-ray diffraction peak position is identified. When the electron transport material can be identified by comparing with the database, the crystal density is determined from the CIF file of the electron transport material described in the database. If the obtained X-ray diffraction profile is not found by comparing it with the database, the molecular structure of the electron transporting material is clarified by chemical analysis (e.g., elemental analysis), and then a single crystal of the electron transporting material is produced and the crystal structure is determined by single crystal X-ray structure analysis. From the obtained crystal structure data, the crystal density is calculated from the volume of the unit cell and the mass of the atoms contained in the unit cell.

[0030] The method for setting the crystal density of the electron transport material within the above range is not particularly limited, but examples include adopting a molecular structure with little steric hindrance, making the electron transport material have a molecular structure with high three-dimensional planarity (for example, having a skeleton that allows intermolecular interactions such as π-π stacking); and specifying the type of electron transport material to include at least one of an electron transport material represented by general formula (P) and an electron transport material represented by general formula (Q) described below.

[0031] The average primary particle size of the electron transporting material is preferably 500 nm or less, more preferably 30 nm or more and 400 nm or less, and even more preferably 50 nm or more and 200 nm or less. ★↑Please add so that it includes the best mode of the example. When the average primary particle size of the electron transporting material is 500 nm or less, the electron transporting material is less likely to localize in the undercoat layer and is more likely to exist with high dispersibility, resulting in superior electron transport properties.When the average primary particle size of the electron transporting material is 30 nm or more, the electron transporting material is less likely to aggregate and is more likely to exist with high dispersibility in the undercoat layer, resulting in superior electron transport properties.

[0032] The average primary particle size of the electron transporting material is determined as follows. The undercoat layer is observed at a magnification of 5000 times by a scanning electron microscope (SEM) in the cross section of the laminate in the thickness direction of the electrophotographic photoreceptor, and the electron transport material is identified. Here, the electron transport material exists as a solid in the binder resin, and the outline can be recognized by a slight step at the interface between the binder resin and the electron transport material. The electron transport material is identified by identifying the outline. Then, the equivalent circle diameters of any 10 particles that exist as primary particles of the electron transporting material present in the obtained SEM image are determined, and the arithmetic mean value of the obtained equivalent circle diameters is regarded as the average primary particle diameter of the electron transporting material.

[0033] The aspect ratio of the electron transporting material is preferably 1.0 or more and 2.5 or less, more preferably 1.2 or more and 2.4 or less, and even more preferably 1.5 or more and 2.3 or less. When the aspect ratio of the electron transporting material is 2.5 or less, the electron transporting material is less likely to be localized in the undercoat layer and is more likely to exist with high dispersibility, resulting in superior electron transport properties.

[0034] The aspect ratio of an electron transporting material means the ratio of the length of the major axis of the electron transporting material to the length of the minor axis of the electron transporting material (major axis length / minor axis length). The length of the electron transport material in the long axis direction refers to the longest linear distance when connecting one end to the other end of the electron transport material in the long axis direction, and the length of the electron transport material in the short axis direction refers to the longest linear distance when connecting one end to the other end of the electron transport material in the direction perpendicular to the long axis.

[0035] The aspect ratio of the electron transporting material is determined as follows. The photosensitive layer (and protective layer, if necessary) is removed from the electrophotographic photoreceptor, and the undercoat layer is observed at 3,000 to 100,000 times magnification using a field emission scanning electron microscope (JSM-6700F manufactured by JEOL) to identify the electron transport material. Here, the electron transport material exists as a solid in the binder resin, and the outline can be recognized by a slight step at the interface between the binder resin and the electron transport material. The electron transport material is identified by identifying the outline. The length of the long axis and the length of the short axis are measured for 100 arbitrary points of the electron transport material from the obtained micrograph, and the aspect ratio (length of the long axis / length of the short axis) is calculated for each point. The arithmetic average value of each aspect ratio is defined as the aspect ratio of the electron transport material.

[0036] The method for adjusting the average primary particle size and aspect ratio of the electron transporting material to fall within the above ranges is not particularly limited, and examples thereof include a method of pulverizing the electron transporting material or a coating liquid for forming an undercoat layer containing the same using a ball mill, a bead mill, a mortar, a sand mill, a kneader, an attritor, or the like, and a method of dissolving the material in fluoroacetic acid, sulfuric acid, or the like and then contacting the material with water or a poor solvent to precipitate microcrystals.

[0037] From the viewpoint of setting the crystal density in the above-mentioned range and setting the full width at half maximum (FWHM) of the maximum intensity peak in an X-ray diffraction spectrum measured in the thickness direction to 5.0° or less, the electron transporting material preferably contains at least one of an electron transporting material represented by the following general formula (P) and an electron transporting material represented by general formula (Q), and more preferably contains an electron transporting material represented by general formula (P). [ka] In the above general formula (P), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, an aralkyl group, an aryl group, an alkoxycarbonyl group, or a halogen atom. In the above general formula (Q), R 51 and R 52 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, an aralkyl group, an aryl group, an alkoxycarbonyl group, or a halogen atom.

[0038] The electron transporting material represented by the general formula (P) and the electron transporting material represented by the general formula (Q) have the property of being excellent in electron transporting property and low in hole transporting property. Therefore, when the undercoat layer contains at least one of the electron transporting material represented by the general formula (P) and the electron transporting material represented by the general formula (Q), the undercoat layer is excellent in electron transporting property and reduces dark decay, and therefore is considered to have excellent charge retention property.

[0039] [Electron transporting material represented by general formula (P)] The electron transporting material represented by formula (P) will be described below.

[0040] [ka]

[0041] In the general formula (P), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, an aralkyl group, an aryl group, an alkoxycarbonyl group, or a halogen atom.

[0042] In the general formula (P), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently preferably represents a hydrogen atom or a halogen atom, and more preferably represents a hydrogen atom. In general formula (P), R 1 ~R 8 When is a hydrogen atom or a halogen atom (more preferably a hydrogen atom), the undercoat layer has better electron transport properties and further reduces dark decay, and is therefore considered to have better charge retention properties.

[0043] In general formula (P), R 1 ~R 8 The alkyl group represented by the formula (I) may be a substituted or unsubstituted alkyl group.

[0044] In general formula (P), R 1 ~R 8Examples of the unsubstituted alkyl group represented by the formula (I) include a linear alkyl group having 1 to 20 carbon atoms (preferably 1 to 10 carbon atoms, more preferably 1 to 6 carbon atoms), a branched alkyl group having 3 to 20 carbon atoms (preferably 3 to 10 carbon atoms), and a cyclic alkyl group having 3 to 20 carbon atoms (preferably 3 to 10 carbon atoms).

[0045] Examples of the linear alkyl group having 1 to 20 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an n-butyl group, an n-pentyl group, an n-hexyl group, an n-heptyl group, an n-octyl group, an n-nonyl group, an n-decyl group, an n-undecyl group, an n-dodecyl group, a tridecyl group, an n-tetradecyl group, an n-pentadecyl group, an n-heptadecyl group, an n-octadecyl group, an n-nonadecyl group, and an n-icosyl group.

[0046] Examples of the branched alkyl group having 3 to 20 carbon atoms include an isopropyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, an isohexyl group, a sec-hexyl group, a tert-hexyl group, an isoheptyl group, a sec-heptyl group, a tert-heptyl group, an isooctyl group, a sec-octyl group, a tert-octyl group, an isononyl group, a sec-nonyl group, a tert-nonyl group, an isodecyl group, a sec-decyl group, a tert-decyl group, an isododecyl group, a sec-dodecyl group, a tert-dodecyl group, a tert-tetradecyl group, and a tert-pentadecyl group.

[0047] Examples of the cyclic alkyl group having 3 to 20 carbon atoms include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, a cyclooctyl group, a cyclononyl group, a cyclodecyl group, and polycyclic (e.g., bicyclic, tricyclic, spirocyclic) alkyl groups formed by linking these monocyclic alkyl groups.

[0048] Among the above, as the unsubstituted alkyl group, a straight-chain alkyl group such as a methyl group or an ethyl group is preferable.

[0049] Substituents in the alkyl group include an alkoxy group, a hydroxy group, a carboxy group, a nitro group, and a halogen atom (such as a fluorine atom, a bromine atom, or an iodine atom). The alkoxy group that substitutes the hydrogen atom in the alkyl group is R 1 ~R 8 Examples of the alkoxy group include the same as the unsubstituted alkoxy group represented by the following formula:

[0050] In general formula (P), R 1 ~R 8 The alkoxy group represented by the following formula (I) includes a substituted or unsubstituted alkoxy group.

[0051] In general formula (P), R 1 ~R 8 Examples of the unsubstituted alkoxy group represented by the formula (I) include linear, branched or cyclic alkoxy groups having 1 to 10 carbon atoms (preferably 1 to 6, more preferably 1 to 4).

[0052] Specific examples of linear alkoxy groups include a methoxy group, an ethoxy group, an n-propoxy group, an n-butoxy group, an n-pentyloxy group, an n-hexyloxy group, an n-heptyloxy group, an n-octyloxy group, an n-nonyloxy group, and an n-decyloxy group. Specific examples of branched alkoxy groups include an isopropoxy group, an isobutoxy group, a sec-butoxy group, a tert-butoxy group, an isopentyloxy group, a neopentyloxy group, a tert-pentyloxy group, an isohexyloxy group, a sec-hexyloxy group, a tert-hexyloxy group, an isoheptyloxy group, a sec-heptyloxy group, a tert-heptyloxy group, an isooctyloxy group, a sec-octyloxy group, a tert-octyloxy group, an isononyloxy group, a sec-nonyloxy group, a tert-nonyloxy group, an isodecyloxy group, a sec-decyloxy group, and a tert-decyloxy group. Specific examples of the cyclic alkoxy group include a cyclopropoxy group, a cyclobutoxy group, a cyclopentyloxy group, a cyclohexyloxy group, a cycloheptyloxy group, a cyclooctyloxy group, a cyclononyloxy group, and a cyclodecyloxy group. Among these, the unsubstituted alkoxy group is preferably a linear alkoxy group.

[0053] Substituents in the alkoxy group include an aryl group, an alkoxycarbonyl group, an aryloxycarbonyl group, a hydroxyl group, a carboxy group, a nitro group and a halogen atom (such as a fluorine atom, a bromine atom or an iodine atom). The aryl group replacing the hydrogen atom in the alkoxy group is, for example, 1 ~R 8 Examples of the unsubstituted aryl group include the same groups as the unsubstituted aryl group represented by the following formula: The alkoxycarbonyl group which replaces the hydrogen atom in the alkoxy group is, for example, 1 ~R 8 Examples of the alkoxycarbonyl group include the unsubstituted alkoxycarbonyl group represented by the following formula: The aryloxycarbonyl group which substitutes the hydrogen atom in the alkoxy group is, for example, 1 ~R 8 Examples of the aryloxycarbonyl group include the unsubstituted aryloxycarbonyl group represented by the following formula:

[0054] In general formula (P), R 1 ~R 8 The aralkyl group represented by the following formula (I) includes a substituted or unsubstituted aralkyl group.

[0055] In general formula (P), R 1 ~R 8 The unsubstituted aralkyl group represented by the following formula is preferably an aralkyl group having 7 to 30 carbon atoms, more preferably an aralkyl group having 7 to 16 carbon atoms, and even more preferably an aralkyl group having 7 to 12 carbon atoms.

[0056] Examples of the unsubstituted aralkyl group having 7 to 30 carbon atoms include a benzyl group, a phenylethyl group, a phenylpropyl group, a 4-phenylbutyl group, a phenylpentyl group, a phenylhexyl group, a phenylheptyl group, a phenyloctyl group, a phenylnonyl group, a naphthylmethyl group, a naphthylethyl group, an anthracylmethyl group, and a phenyl-cyclopentylmethyl group.

[0057] Substituents in the aralkyl group include an alkoxy group, an alkoxycarbonyl group, and a halogen atom (such as a fluorine atom, a bromine atom, an iodine atom, etc.). The alkoxy group which substitutes the hydrogen atom in the aralkyl group is, for example, 1 ~R 8 Examples of the alkoxy group include the same as the unsubstituted alkoxy group represented by the following formula: The alkoxycarbonyl group which substitutes a hydrogen atom in the aralkyl group is, for example, 1 ~R 8 Examples of the alkoxycarbonyl group include the unsubstituted alkoxycarbonyl group represented by the following formula:

[0058] In general formula (P), R 1 ~R 8 The aryl group represented by the formula (I) may be a substituted or unsubstituted aryl group.

[0059] In general formula (P), R 1 ~R 8 The unsubstituted aryl group represented by the following formula is preferably an aryl group having 6 to 30 carbon atoms, more preferably an aryl group having 6 to 14 carbon atoms, and even more preferably an aryl group having 6 to 10 carbon atoms.

[0060] Examples of the aryl group having 6 to 30 carbon atoms include a phenyl group, a biphenyl group, a 1-naphthyl group, a 2-naphthyl group, a 9-anthryl group, a 9-phenanthryl group, a 1-pyrenyl group, a 5-naphthacenyl group, a 1-indenyl group, a 2-azulenyl group, a 9-fluorenyl group, a biphenylenyl group, an indacenyl group, a fluoranthenyl group, an acenaphthylenyl group, an aceanthryllenyl group, a phenalenyl group, and a fluorenyl group. Examples of the anthryl group include anthryl, bianthracenyl, teranthracenyl, quaternary anthracenyl, anthraquinolyl, phenanthryl, triphenylenyl, pyrenyl, chrysenyl, naphthacenyl, pleiadenyl, picenyl, perylenyl, pentaphenyl, pentacenyl, tetraphenylenyl, hexaphenyl, hexacenyl, rubicenyl, and coronenyl groups. Of the above, the phenyl group is preferred.

[0061] Substituents in the aryl group include an alkyl group, an alkoxy group, an alkoxycarbonyl group, an aryloxycarbonyl group, and a halogen atom (such as a fluorine atom, a bromine atom, or an iodine atom). The alkyl group that substitutes the hydrogen atom in the aryl group is, for example, 1 ~R 8 Examples of the unsubstituted alkyl group include the same groups as the unsubstituted alkyl group represented by the following formula: The alkoxy group which substitutes the hydrogen atom in the aryl group is, in the general formula (P), R 1 ~R 8 Examples of the alkoxy group include the same as the unsubstituted alkoxy group represented by the following formula: The alkoxycarbonyl group which substitutes the hydrogen atom in the aryl group is, in general formula (P), R 1 ~R 8 Examples of the alkoxycarbonyl group include the unsubstituted alkoxycarbonyl group represented by the following formula:

[0062] In general formula (P), R 1 ~R 8 The alkoxycarbonyl group represented by the following formula (I) includes a substituted or unsubstituted alkoxycarbonyl group.

[0063] In general formula (P), R1 ~R 8 The number of carbon atoms in the alkyl chain in the unsubstituted alkoxycarbonyl group represented by the following formula is preferably 1 or more and 20 or less, more preferably 1 or more and 15 or less, and even more preferably 1 or more and 10 or less.

[0064] Examples of the alkoxycarbonyl group having an alkyl chain carbon number of 1 to 20 include a methoxycarbonyl group, an ethoxycarbonyl group, a propoxycarbonyl group, an isopropoxycarbonyl group, an n-butoxycarbonyl group, a sec-butoxybutylcarbonyl group, a tert-butoxycarbonyl group, a pentaoxycarbonyl group, a hexaoxycarbonyl group, a heptoxycarbonyl group, an octaoxycarbonyl group, a nonaoxycarbonyl group, a decaoxycarbonyl group, a dodecaoxycarbonyl group, a tridecaoxycarbonyl group, a tetradecaoxycarbonyl group, a pentadecaoxycarbonyl group, a hexadecaoxycarbonyl group, a heptadecaoxycarbonyl group, an octadecaoxycarbonyl group, a nonadecaoxycarbonyl group, and an icosaoxycarbonyl group.

[0065] Substituents in the alkoxycarbonyl group include an aryl group, a hydroxy group and a halogen atom (such as a fluorine atom, a bromine atom, an iodine atom, etc.). The aryl group replacing the hydrogen atom in the alkoxycarbonyl group is, for example, 1 ~R 8 Examples of the unsubstituted aryl group include the same groups as the unsubstituted aryl group represented by the following formula:

[0066] In general formula (P), R 1 ~R 8 Examples of the halogen atom represented by the formula (I) include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0067] Exemplary compounds of the electron transport material represented by general formula (P) are shown below, but the present embodiment is not limited thereto. Note that the following exemplary compound numbers are hereinafter expressed as exemplary compound (P-number).

[0068] [ka]

[0069] [ka]

[0070] [Electron transporting material represented by general formula (Q)] The electron transporting material represented by formula (Q) will be described below.

[0071] [ka]

[0072] In general formula (Q), R 51 and R 52 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, an aralkyl group, an aryl group, an alkoxycarbonyl group, or a halogen atom.

[0073] In general formula (Q), R 51 and R 52 each independently preferably represents a hydrogen atom or a halogen atom, and more preferably represents a hydrogen atom. In general formula (Q), R 51 and R 52 When is a hydrogen atom or a halogen atom (more preferably a hydrogen atom), the undercoat layer has better electron transport properties and further reduces dark decay, and is therefore considered to have better charge retention properties.

[0074] In general formula (Q), R 51 ~R 52 The alkyl group, alkoxy group, aralkyl group, aryl group, alkoxycarbonyl group, and halogen atom represented by the formula (P) are 11 ~R 18Examples of the alkyl group, alkoxy group, aralkyl group, aryl group, alkoxycarbonyl group, and halogen atom represented by the following formula are mentioned.

[0075] In general formula (Q), R 51 ~R 52 The alkyl group, alkoxy group, aralkyl group, aryl group and alkoxycarbonyl group represented by R in the general formula (P) are 11 ~R 18 These groups may have the same substituents as those exemplified for the alkyl group, alkoxy group, aralkyl group, aryl group and alkoxycarbonyl group represented by the following formula:

[0076] In general formula (Q), R 51 ~R 52 may each independently be represented by a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 12 carbon atoms, a cycloalkyl group, an aryl group, or an aralkyl group.

[0077] Exemplary compounds of the electron transport material represented by general formula (Q) are shown below, but the present embodiment is not limited thereto. Note that the following exemplary compound numbers are hereinafter referred to as exemplary compound (Q-number).

[0078] [ka]

[0079] [ka]

[0080] The abbreviations and the like in the above exemplary compounds have the following meanings. Ph: Phenyl group ·OCH 3 :Methoxy group tC 4 H 9 O: t-butoxy group ·cC 6 H 11 : Cyclohexyl group C 6 H 5 : Phenyl group ·CH 2 C 6 H 5 : Benzyl group 3,5-(CH 3 ) 2 -C 6 H 3 : 3,5-Dimethylphenyl group 3,5-Cl 2 -C 6 H 3 : 3,5-dichlorophenyl group Br: Bromine atom Cl: Chlorine atom

[0081] The undercoat layer may further contain an electron transporting material other than the electron transporting material represented by general formula (P) and the electron transporting material represented by general formula (Q) within the range in which the effects of the present disclosure are achieved. The proportion of the total amount of the electron transport material represented by general formula (P) and the electron transport material represented by general formula (Q) in the total amount of the electron transport materials in the undercoat layer is preferably 80% by mass or more and 100% by mass or less, more preferably 90% by mass or more and 100% by mass or less, and even more preferably 95% by mass or more and 100% by mass or less.

[0082] The content of the electron transporting material is preferably 60% by mass or more, more preferably 60% by mass or more and 80% by mass or less, and even more preferably 65% ​​by mass or more and 75% by mass or less, based on the total binder resin component content of the undercoat layer. When the content of the electron transporting material is 80% by mass or less, the film quality becomes brittle, film formability decreases, and the occurrence of surface roughness of the undercoat layer is suppressed, resulting in both excellent electron transporting properties and charge retention properties.On the other hand, when the content of the electron transporting material is 60% by mass or more, the occurrence of excess or deficiency in the electron transporting ability is suppressed, resulting in both excellent electron transporting properties and charge retention properties.

[0083] , The content of the electron transporting material may be less than 60% by mass, 45% by mass or more and less than 60% by mass, or 50% by mass or more and less than 60% by mass, based on the total binder resin component content of the undercoat layer. In this embodiment, the crystal density is 1.62 g / cm 3 or more, and the full width at half maximum (FWHM) of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction is 5.0° or less. Therefore, even if the content of the electron transport material is less than 60 mass %, the electrostatic charge retention ability and electron transport property are excellent.

[0084] (Binding resin) Examples of the binder resin used in the undercoat layer include known materials such as acetal resins (e.g., polyvinyl butyral, etc.), polyvinyl alcohol resins, polyvinyl acetal resins, casein resins, polyamide resins, cellulose resins, gelatin, polyurethane resins, polyester resins, unsaturated polyester resins, methacrylic resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, vinyl chloride-vinyl acetate-maleic anhydride resins, silicone resins, silicone-alkyd resins, urea resins, phenol resins, phenol-formaldehyde resins, melamine resins, urethane resins, alkyd resins, and epoxy resins; zirconium chelate compounds; titanium chelate compounds; aluminum chelate compounds; titanium alkoxide compounds; organic titanium compounds; and silane coupling agents. Examples of the binder resin used in the undercoat layer include charge transporting resins having charge transporting groups, conductive resins (such as polyaniline, etc.), and the like.

[0085] Among these, the binder resin used in the undercoat layer is preferably a resin that is insoluble in the coating solvent of the upper layer, and in particular, a resin obtained by reacting at least one resin selected from the group consisting of thermosetting resins such as urea resins, phenol resins, phenol-formaldehyde resins, melamine resins, urethane resins, unsaturated polyester resins, alkyd resins, and epoxy resins, with a curing agent is preferred. When two or more of these binder resins are used in combination, the mixing ratio is set as necessary. In this specification, the urethane resin obtained by the reaction of a resin with a curing agent is also referred to as a "curable urethane resin" for convenience.

[0086] (Inorganic particles) The undercoat layer may further contain inorganic particles. As inorganic particles, for example, powder resistivity (volume resistivity) of 10 2 Ωcm or more 10 11 Examples of such particles include inorganic particles with a particle size of Ωcm or less. Among these, examples of inorganic particles having the above-mentioned resistance value include metal oxide particles such as tin oxide particles, titanium oxide particles, zinc oxide particles, and zirconium oxide particles, and zinc oxide particles are particularly preferred.

[0087] The specific surface area of ​​inorganic particles by the BET method is, for example, 10 m 2 / g or more is preferable. The specific surface area is 10m 2 When the molecular weight is 1.0 or more, the decrease in electrostatic chargeability tends to be suppressed. The volume average particle size of the inorganic particles is, for example, from 50 nm to 2000 nm (preferably from 60 nm to 1000 nm).

[0088] The content of the inorganic particles is, for example, preferably from 0% by mass to 80% by mass, and more preferably from 0% by mass to 70% by mass, based on the total solid content of the undercoat layer.

[0089] The inorganic particles may be surface-treated. Two or more types of inorganic particles having different surface treatments or different particle sizes may be used in combination.

[0090] Examples of the surface treatment agent include a silane coupling agent, a titanate coupling agent, an aluminum coupling agent, a surfactant, etc. In particular, a silane coupling agent is preferred, and a silane coupling agent having an amino group is more preferred.

[0091] Examples of silane coupling agents having an amino group include, but are not limited to, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, and N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane.

[0092] The silane coupling agent may be used in combination of two or more kinds. For example, The silane coupling agent may be used in combination with other silane coupling agents. Examples of the other silane coupling agents include, but are not limited to, vinyltrimethoxysilane, 3-methacryloxypropyl-tris(2-methoxyethoxy)silane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, and 3-chloropropyltrimethoxysilane.

[0093] The surface treatment method using the surface treatment agent may be any known method, and may be either a dry method or a wet method.

[0094] The amount of the surface treatment agent to be used is preferably, for example, 0.5% by mass or more and 10% by mass or less based on the inorganic particles.

[0095] The dry method is, for example, a method in which a surface treatment agent is attached to the surface of inorganic particles by dropping a surface treatment agent directly or dissolved in an organic solvent or spraying it together with dry air or nitrogen gas while stirring inorganic particles with a mixer or the like that exerts a large shearing force. The dropping or spraying of the surface treatment agent is preferably performed at a temperature below the boiling point of the solvent. After dropping or spraying the surface treatment agent, baking may be performed at 100° C. or higher. The temperature and time of baking are not particularly limited as long as electrophotographic properties can be obtained.

[0096] The wet method is a method in which, for example, by stirring, ultrasonic waves, a sand mill, an attritor, a ball mill, or the like, inorganic particles are dispersed in a solvent, a surface treatment agent is added, and the mixture is stirred or dispersed, and then the solvent is removed to attach the surface treatment agent to the surface of the inorganic particles. The solvent is removed, for example, by filtration or distillation. After the solvent is removed, baking may be performed at 100° C. or higher. The baking temperature and time are not particularly limited as long as electrophotographic properties are obtained. In the wet method, moisture contained in the inorganic particles may be removed before the addition of the surface treatment agent, and examples of such methods include a method of removing the moisture while stirring and heating in a solvent, and a method of removing the moisture by azeotropy with the solvent.

[0097] (Other materials) The undercoat layer may further contain various additives for improving electrical properties, environmental stability, and image quality. Examples of the additives include known materials such as polycyclic condensation and azo-based electron transporting materials, zirconium chelate compounds, titanium chelate compounds, aluminum chelate compounds, titanium alkoxide compounds, organic titanium compounds, silane coupling agents, etc. As described above, silane coupling agents are used for surface treatment of inorganic particles, and may also be added to the undercoat layer as an additive.

[0098] Examples of silane coupling agents as additives include vinyltrimethoxysilane, 3-methacryloxypropyl-tris(2-methoxyethoxy)silane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, and the like.

[0099] Examples of the zirconium chelate compound include zirconium butoxide, zirconium ethyl acetoacetate, zirconium triethanolamine, acetylacetonate zirconium butoxide, ethyl acetoacetate zirconium butoxide, zirconium acetate, zirconium oxalate, zirconium lactate, zirconium phosphonate, zirconium octanoate, zirconium naphthenate, zirconium laurate, zirconium stearate, zirconium isostearate, methacrylate zirconium butoxide, stearate zirconium butoxide, and isostearate zirconium butoxide.

[0100] Examples of titanium chelate compounds include tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, titanium acetylacetonate, polytitanium acetylacetonate, titanium octylene glycolate, titanium lactate ammonium salt, titanium lactate, titanium lactate ethyl ester, titanium triethanolamine, and polyhydroxytitanium stearate.

[0101] Examples of aluminum chelate compounds include aluminum isopropylate, monobutoxyaluminum diisopropylate, aluminum butyrate, diethylacetoacetate aluminum diisopropylate, and aluminum tris(ethylacetoacetate).

[0102] These additives may be used alone or as a mixture or polycondensation product of a plurality of compounds.

[0103] -Characteristics of the undercoat layer- The undercoat layer has a full width at half maximum (FWHM) of the maximum intensity peak in X-ray diffraction measurement in the thickness direction of 5.0° or less, preferably 3.0° or less, more preferably 1.0° or less, and particularly preferably 0.7° or less. When the full width at half maximum (FWHM) of the maximum intensity peak is 5.0° or less, there are few defects in the crystal structure and the crystals are regularly arranged, resulting in superior electron transport properties.

[0104] There is no particular limitation on the method for adjusting the full width at half maximum of the maximum intensity peak to fall within the above range, and examples of such methods include adjusting the average primary particle size, aspect ratio, etc. of the electron transporting material in the undercoat layer.

[0105] The relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer is I 1 The relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured by powdering the undercoat layer with a volume average particle size of 5 μm or less was defined as I 2 In this case, the maximum value Nmax of the orientation index N represented by the following formula (1) is preferably 1.0 or more and 5.5 or less, more preferably 3.0 or more and 5.3 or less, and even more preferably 4.0 or more and 5.1 or less.

[0106]

number

[0107] In the present disclosure, the "maximum intensity peak" refers to the strongest crystal diffraction peak in an X-ray diffraction spectrum measured when the undercoat layer is in a powder state having a volume average particle size of 5 μm or less. In the present disclosure, the relative integrated intensity of the maximum intensity peak is the integral of the intensity of the maximum intensity peak minus the intensity of the background, and the subtraction of the intensity of the background is performed by the Shirley method. For example, the orientation index N at a certain maximum intensity peak A, expressed by formula (1), is the value obtained by dividing the value of the relative integrated intensity of a certain peak A in an X-ray diffraction measurement / the relative integrated intensity of all peaks by the value of the relative integrated intensity of a certain maximum intensity peak A in an X-ray diffraction measurement measured when the undercoat layer is in a powder state with a volume average particle size of 5 μm or less / the relative integrated intensity of all peaks in an X-ray diffraction measurement measured when the undercoat layer is in a powder state with a volume average particle size of 5 μm or less. Among the orientation indices N, which are expressed by the formula (1), found for each peak, the largest value is the value of Nmax. In addition, when the undercoat layer is in a powder state with a volume average particle size of 5 μm or less, it is presumed that the orientation state is random. Therefore, it is presumed that the smaller the maximum value Nmax of the orientation index N expressed by the above formula (1) is, the less the crystal orientation in the undercoat layer is, and the more random the arrangement of the crystal directions of the electron transport material in the undercoat layer is.

[0108] In the present disclosure, the full width at half maximum (FWHM) of the maximum intensity peak and the maximum value Nmax of the orientation index N are determined by X-ray diffraction measurement under measurement conditions. Measurement equipment: Bruker AEX Co., Ltd., D8DISCOVER X-ray source:CuKα Measurement method: 2θ / θ scan However, other X-ray sources such as Cr, Fe, Co, and Mo may also be used, and the measurement range must be set so that all diffraction peaks derived from the powdered electron transport compound can be detected.

[0109] The undercoat layer may be converted into a powder having a volume average particle size of 5 μm or less by any method, such as a method of pulverizing the undercoat layer using a ball mill, a bead mill, a mortar, a sand mill, a kneader, an attritor, or the like, or a method of dissolving the undercoat layer in fluoroacetic acid, sulfuric acid, or the like, and then contacting the resulting mixture with water or a poor solvent to precipitate fine crystals. The pulverizing treatment may be performed under either a dry method or a wet method. It is preferable to use inorganic compounds such as table salt and mirabilite, or grinding media such as glass beads, steel beads, alumina beads, and zirconia beads during pulverization, since this makes it easier to obtain uniform crystals. In the case of a wet method, any processing solvent such as water, alcohol, or an organic solvent may be used in order to further control the crystal shape and size of the particles.

[0110] The method for adjusting the maximum value Nmax to be within the above range is not particularly limited, and examples thereof include a method for adjusting the average primary particle size, aspect ratio, etc. of the electron transporting material in the undercoat layer.

[0111] The undercoat layer preferably has a LUMO energy level of 3.8 eV or more and 4.2 eV or less, more preferably 3.9 eV or more and 4.2 eV or less, and even more preferably 4.0 eV or more and 4.2 eV or less. When the LUMO energy level of the undercoat layer is 4.2 eV or less, the charge retention is excellent, whereas when the LUMO energy level of the undercoat layer is 3.8 eV or more, the electron injection from the charge generating layer is excellent.

[0112] The method for adjusting the LUMO energy level of the undercoat layer to fall within the above range is not particularly limited, and examples thereof include a method of adjusting the type of electron transporting material (more preferably, the electron transporting material is designed to contain at least one of an electron transporting material represented by general formula (P) and an electron transporting material represented by general formula (Q)).

[0113] The LUMO energy level of the undercoat layer is determined as follows. After cutting the electrophotographic photoreceptor into 2 cm squares from the outer peripheral surface side in the lamination direction, the photosensitive layer is removed using a solvent such as THF to obtain a sample consisting of only the conductive substrate and undercoat layer. The prepared sample is measured from the outer peripheral surface side of the electrophotographic photoreceptor (i.e., from the undercoat layer side) with an atmospheric photoelectron yield spectrometer AC-2 manufactured by RIKEN in the range of 4 eV to 6.2 eV at a measurement light intensity of 500 nm to obtain a spectrum graph with the horizontal axis representing the energy of the irradiated light and the vertical axis representing the electron concentration rate. In this spectrum graph, the intersection point between the baseline and a straight line drawn at the rising portion of the plot from the baseline is defined as E HOMO Next, the single undercoat layer film peeled off from the substrate was measured by the transmission method using an ultraviolet-visible-near infrared (UV-Vis-NIR) spectrophotometer (model: Cary5000, manufactured by Agilent Technologies) in the range of wavelengths from 200 nm to 800 nm, and the absorption edge in the range of wavelengths from 400 nm to 700 nm was calculated, which was taken as the energy gap (HOMO-LUMO energy difference △E). LUMO was calculated using the following formula. Formula: LUMO=HOMO+△E

[0114] The volume resistivity of the undercoat layer is 1×10 10 Ωcm or more 1×10 12 It is preferable that the resistivity is Ωcm or less.

[0115] The undercoat layer preferably has a Vickers hardness of 35 or more. The surface roughness (ten-point average roughness) of the undercoat layer is preferably adjusted to between 1 / (4n) (n is the refractive index of the upper layer) and 1 / 2 of the wavelength λ of the exposure laser used in order to suppress moire images. Resin particles or the like may be added to the undercoat layer to adjust the surface roughness. Examples of the resin particles include silicone resin particles and crosslinked polymethyl methacrylate resin particles. The surface of the undercoat layer may be polished to adjust the surface roughness. Examples of the polishing method include buffing, sandblasting, wet honing, grinding, and the like.

[0116] - Method for forming undercoat layer - The formation of the undercoat layer is not particularly limited, and a well-known formation method can be used. For example, the undercoat layer can be formed by forming a coating film of a coating solution for forming the undercoat layer in which the above-mentioned components are added to a solvent, drying the coating film, and heating it as necessary.

[0117] Examples of the solvent for preparing the coating liquid for forming the undercoat layer include known organic solvents, such as alcohol-based solvents, aromatic hydrocarbon solvents, halogenated hydrocarbon solvents, ketone-based solvents, ketone alcohol-based solvents, ether-based solvents, and ester-based solvents. Specific examples of these solvents include ordinary organic solvents such as methanol, ethanol, n-propanol, iso-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, methylene chloride, chloroform, chlorobenzene, and toluene.

[0118] Examples of the method for dispersing the inorganic particles when preparing the coating liquid for forming the undercoat layer include known methods such as those using a roll mill, a ball mill, a vibrating ball mill, an attritor, a sand mill, a colloid mill, and a paint shaker.

[0119] Since the electron transport material (particularly the electron transport material represented by the general formula (P)) is difficult to dissolve in an organic solvent, it is preferable to disperse it in the organic solvent. Examples of the dispersion method include known methods such as a roll mill, a ball mill, a vibrating ball mill, an attritor, a sand mill, a colloid mill, and a paint shaker. When metal oxide particles are blended in the undercoat layer, it is preferable to disperse the metal oxide particles in the organic solvent by the same dispersion method.

[0120] Examples of the method for applying the coating liquid for forming the undercoat layer onto the conductive substrate include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.

[0121] The metal oxide content in the undercoat layer is preferably 5 mass% or less, more preferably 3 mass% or less, and even more preferably 0 mass% (i.e., no metal oxide) or 2 mass% or less, based on the total solid content of the undercoat layer. In general, metal oxides tend to have low resistance. Therefore, if the content of metal oxide in the undercoat layer is 5 mass% or less, the resistance of the undercoat layer is low, and the decrease in electron transport property and charge retention property is suppressed. In addition, it is preferable to reduce the content of metal oxide from the viewpoint of manufacturing aimed at reducing the environmental load.

[0122] The thickness of the undercoat layer is preferably from 5 μm to 15 μm, more preferably from 7 μm to 14 μm, and even more preferably from 8 μm to 13 μm. The thickness of the undercoat layer may be 15 μm or more, or may be from 20 μm to 50 μm.

[0123] Conventional electron transporting materials have a slight hole transporting property in addition to electron transporting property, so that the thickness of the undercoat layer is made thin (for example, 5 μm or less), and image defects caused by the injection of electric charges from the conductive substrate into the photosensitive layer and the reduction of the surface charge are suppressed. However, if the thickness of the undercoat layer is thin, for example, when needle-shaped foreign matter is mixed in from a developing means (for example, a developing device, etc.) or a transfer means (for example, an intermediate transfer body, etc.) during image formation, the needle-shaped foreign matter may penetrate from the surface of the electrophotographic photoreceptor to the undercoat layer, and the charge retention property may decrease due to leakage current. In contrast, in this embodiment, since the undercoat layer contains an electron transporting material represented by general formula (P) that has excellent electron transporting property and low hole transporting property, the thickness can be made thicker than conventional undercoat layers (for example, 5 μm or more). Therefore, even if a needle-shaped foreign matter penetrates from the surface of the electrophotographic photoreceptor to the undercoat layer, leakage current is unlikely to occur, and the charge retention property is considered to be excellent. When the thickness of the undercoat layer is 15 μm or less, the leakage current in the bulk is generated, and the electric charge remaining in the undercoat layer is increased, which suppresses the increase in dark decay, and as a result, it is believed that the charge retention is improved.

[0124] [Conductive substrate] Examples of conductive substrates include metal plates, metal drums, and metal belts containing metals (aluminum, copper, zinc, chromium, nickel, molybdenum, vanadium, indium, gold, platinum, etc.) or alloys (stainless steel, etc.). Examples of conductive substrates include paper, resin films, belts, etc. coated, vapor-deposited, or laminated with conductive compounds (e.g., conductive polymers, indium oxide, etc.), metals (e.g., aluminum, palladium, gold, etc.) or alloys. Here, "conductive" refers to a material having a volume resistivity of 10 13 This means that the resistance is less than Ωcm.

[0125] When the electrophotographic photoreceptor is used in a laser printer, the surface of the conductive substrate is preferably roughened to a center line average roughness Ra of 0.04 μm to 0.5 μm in order to suppress interference fringes that occur when irradiating with laser light. When non-interfering light is used as the light source, roughening to prevent interference fringes is not particularly necessary, but it is suitable for extending the life of the conductive substrate since it suppresses the occurrence of defects due to unevenness on the surface.

[0126] Examples of methods for roughening the surface include wet honing, which involves spraying an abrasive suspended in water onto the conductive substrate; centerless grinding, in which the conductive substrate is pressed against a rotating grindstone and continuously ground; and anodizing.

[0127] As a method for roughening the surface, there can be mentioned a method in which, without roughening the surface of the conductive substrate, a conductive or semiconductive powder is dispersed in a resin to form a layer on the surface of the conductive substrate, and the surface is roughened by the particles dispersed in the layer.

[0128] In the roughening treatment by anodization, a conductive substrate made of metal (e.g., aluminum) is used as the anode and anodized in an electrolyte solution to form an oxide film on the surface of the conductive substrate. Examples of electrolyte solutions include sulfuric acid solutions and oxalic acid solutions. However, the porous anodic oxide film formed by anodization is chemically active in its original state, easily contaminated, and has a large resistance variation depending on the environment. Therefore, it is preferable to perform a sealing treatment on the porous anodic oxide film, in which the micropores of the oxide film are sealed by volume expansion caused by hydration reaction in pressurized steam or boiling water (metal salts such as nickel may be added) to change the film into a more stable hydrated oxide.

[0129] The thickness of the anodic oxide film is preferably, for example, from 0.3 μm to 15 μm. If the thickness is within this range, the film tends to exhibit a barrier property against injection and tends to suppress an increase in residual potential due to repeated use.

[0130] The conductive substrate may be subjected to a treatment with an acidic treatment solution or a boehmite treatment. Treatment with an acid treatment liquid is carried out, for example, as follows. First, an acid treatment liquid containing phosphoric acid, chromic acid, and hydrofluoric acid is prepared. The compounding ratios of phosphoric acid, chromic acid, and hydrofluoric acid in the acid treatment liquid are, for example, in the range of 10% by mass to 11% by mass for phosphoric acid, 3% by mass to 5% by mass for chromic acid, and 0.5% by mass to 2% by mass for hydrofluoric acid, and the total concentration of these acids is preferably in the range of 13.5% by mass to 18% by mass. The treatment temperature is preferably, for example, 42° C. to 48° C. The film thickness of the coating is preferably 0.3 μm to 15 μm.

[0131] The boehmite treatment is carried out, for example, by immersing the plate in pure water at 90° C. to 100° C. for 5 to 60 minutes, or by contacting the plate with heated steam at 90° C. to 120° C. for 5 to 60 minutes. The thickness of the coating is preferably 0.1 μm to 5 μm. This may be further anodized using an electrolyte solution having low coating solubility, such as adipic acid, boric acid, borates, phosphates, phthalates, maleates, benzoates, tartrates, or citrates.

[0132] (Middle class) Although not shown, an intermediate layer may be further provided between the undercoat layer and the photosensitive layer. The intermediate layer is, for example, a layer containing a resin. Examples of the resin used in the intermediate layer include polymer compounds such as acetal resins (e.g., polyvinyl butyral, etc.), polyvinyl alcohol resins, polyvinyl acetal resins, casein resins, polyamide resins, cellulose resins, gelatin, polyurethane resins, polyester resins, methacrylic resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, vinyl chloride-vinyl acetate-maleic anhydride resins, silicone resins, silicone-alkyd resins, phenol-formaldehyde resins, and melamine resins. The intermediate layer may be a layer containing an organometallic compound. Examples of the organometallic compound used in the intermediate layer include organometallic compounds containing metal atoms such as zirconium, titanium, aluminum, manganese, and silicon. The compounds used in the intermediate layer may be used alone or as a mixture or polycondensation product of a plurality of compounds.

[0133] Among these, the intermediate layer is preferably a layer containing an organometallic compound containing zirconium atoms or silicon atoms.

[0134] The formation of the intermediate layer is not particularly limited, and a well-known formation method can be used. For example, the intermediate layer can be formed by forming a coating film of a coating liquid for forming an intermediate layer in which the above components are added to a solvent, drying the coating film, and heating it if necessary. The intermediate layer can be formed by any of the usual coating methods, such as dip coating, push-up coating, wire bar coating, spray coating, blade coating, knife coating and curtain coating.

[0135] The thickness of the intermediate layer is preferably set in the range of, for example, 0.1 μm to 3 μm. The intermediate layer may also be used as an undercoat layer.

[0136] (Charge generation layer) The charge generation layer is, for example, a layer containing a charge generation material and a binder resin. The charge generation layer may also be a vapor deposition layer of the charge generation material. The vapor deposition layer of the charge generation material is suitable for use with a non-coherent light source such as an LED (Light Emitting Diode) or an organic EL (Electro-Luminescence) image array.

[0137] Examples of the charge generating material include azo pigments such as bisazo and trisazo; condensed aromatic pigments such as dibromoanthanthrone; perylene pigments; pyrrolopyrrole pigments; phthalocyanine pigments; zinc oxide; and trigonal selenium.

[0138] Among these, in order to accommodate laser exposure in the near infrared region, it is preferable to use a metal phthalocyanine pigment or a metal-free phthalocyanine pigment as the charge generating material, specifically, for example, hydroxygallium phthalocyanine, chlorogallium phthalocyanine, dichlorotin phthalocyanine, or titanyl phthalocyanine.

[0139] On the other hand, in order to accommodate laser exposure in the near ultraviolet region, preferred charge generating materials include condensed aromatic pigments such as dibromoanthanthrone, thioindigo pigments, porphyrazine compounds, zinc oxide, trigonal selenium, and bisazo pigments.

[0140] The above charge generating material may be used when using an incoherent light source such as an LED or an organic EL image array that emits light at a central wavelength of 450 nm or more and 780 nm or less, but from the viewpoint of resolution, when using a photosensitive layer that is a thin film of 20 μm or less, the electric field strength in the photosensitive layer becomes high, and a decrease in charging due to charge injection from the substrate, that is, an image defect called a black spot, is likely to occur. This becomes noticeable when a charge generating material that is a p-type semiconductor that is likely to generate dark current, such as trigonal selenium or a phthalocyanine pigment, is used.

[0141] In contrast, when an n-type semiconductor such as a fused aromatic pigment, a perylene pigment, or an azo pigment is used as the charge generating material, dark current is unlikely to occur, and image defects called black spots can be suppressed even when the material is made into a thin film. The n-type is determined by the polarity of the photocurrent that flows using the commonly used time-of-flight method, and those that easily pass electrons as carriers rather than holes are considered to be n-type.

[0142] The binder resin used in the charge generating layer may be selected from a wide range of insulating resins, and may also be selected from organic photoconductive polymers such as poly-N-vinylcarbazole, polyvinylanthracene, polyvinylpyrene, polysilane, and the like. Examples of the binder resin include polyvinyl butyral resin, polyarylate resin (polycondensation product of bisphenols and aromatic dicarboxylic acid, etc.), polycarbonate resin, polyester resin, phenoxy resin, vinyl chloride-vinyl acetate copolymer, polyamide resin, acrylic resin, polyacrylamide resin, polyvinylpyridine resin, cellulose resin, urethane resin, epoxy resin, casein, polyvinyl alcohol resin, polyvinylpyrrolidone resin, etc. Here, "insulating" means a material having a volume resistivity of 10 13 This means that the resistance is Ωcm or more. These binder resins may be used alone or in combination of two or more.

[0143] The mixing ratio of the charge generating material to the binder resin is in the range of 10:1 to 1:10 by mass. It is preferable that the temperature is within 100° C.

[0144] The charge generating layer may contain other well-known additives.

[0145] The formation of the charge generation layer is not particularly limited, and a known formation method is used, for example, by forming a coating film of a coating solution for forming a charge generation layer in which the above-mentioned components are added to a solvent, drying the coating film, and heating it as necessary. The formation of the charge generation layer may be performed by vapor deposition of a charge generation material. The formation of the charge generation layer by vapor deposition is particularly suitable when a condensed ring aromatic pigment or a perylene pigment is used as the charge generation material.

[0146] Examples of the solvent for preparing the coating liquid for forming the charge generating layer include methanol, ethanol, n-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, methylene chloride, chloroform, chlorobenzene, toluene, etc. These solvents may be used alone or in combination of two or more.

[0147] Examples of methods for dispersing particles (e.g., charge generating material) in the coating liquid for forming a charge generating layer include media dispersers such as ball mills, vibration ball mills, attritors, sand mills, and horizontal sand mills, and medialess dispersers such as stirrers, ultrasonic dispersers, roll mills, and high-pressure homogenizers. Examples of high-pressure homogenizers include a collision method in which the dispersion liquid is dispersed by liquid-liquid collision or liquid-wall collision under high pressure, and a penetration method in which the dispersion liquid is dispersed by penetrating a fine flow path under high pressure. During this dispersion, it is effective to adjust the average particle size of the charge generating material in the coating liquid for forming the charge generating layer to 0.5 μm or less, preferably 0.3 μm or less, and more preferably 0.15 μm or less.

[0148] Examples of a method for applying the coating liquid for forming the charge generating layer onto the undercoat layer (or onto the intermediate layer) include conventional methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.

[0149] The thickness of the charge generating layer is set, for example, preferably in the range of 0.1 μm or more and 5.0 μm or less, and more preferably in the range of 0.2 μm or more and 2.0 μm or less.

[0150] (charge transport layer) The charge transport layer is, for example, a layer containing a charge transport material and a binder resin, and may be a layer containing a polymer charge transport material.

[0151] Examples of the charge transport material include electron transporting compounds such as quinone compounds such as p-benzoquinone, chloranil, bromanil, and anthraquinone; tetracyanoquinodimethane compounds; fluorenone compounds such as 2,4,7-trinitrofluorenone; xanthone compounds; benzophenone compounds; cyanovinyl compounds; and ethylene compounds. Examples of the charge transport material include hole transporting compounds such as triarylamine compounds, benzidine compounds, arylalkane compounds, aryl-substituted ethylene compounds, stilbene compounds, anthracene compounds, and hydrazone compounds. These charge transport materials may be used alone or in combination, but are not limited to these.

[0152] As the charge transport material, from the viewpoint of charge mobility, a triarylamine derivative represented by the following structural formula (a-1) and a benzidine derivative represented by the following structural formula (a-2) are preferable.

[0153] [ka]

[0154] In structural formula (a-1), Ar T1 , Ar T2 , and Ar T3 each independently represents a substituted or unsubstituted aryl group; 6 H 4 -C(R T4 )=C(R T5 )(R T6 ), or -C 6 H 4 -CH=CH-CH=C(RT7 )(R T8 ) is shown. T4 , R T5 , R T6 , R T7 , and R T8 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group. Examples of the substituent for each of the above groups include a halogen atom, an alkyl group having from 1 to 5 carbon atoms, and an alkoxy group having from 1 to 5 carbon atoms. Examples of the substituent for each of the above groups also include a substituted amino group substituted with an alkyl group having from 1 to 3 carbon atoms.

[0155] [ka]

[0156] In structural formula (a-2), R T91 and R T92 R each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 carbon atoms. T101 , R T102 , R T111 and R T112 each independently represents a halogen atom, an alkyl group having from 1 to 5 carbon atoms, an alkoxy group having from 1 to 5 carbon atoms, an amino group substituted with an alkyl group having from 1 to 2 carbon atoms, a substituted or unsubstituted aryl group, -C(R T12 )=C(R T13 )(R T14 ), or -CH=CH-CH=C(R T15 )(R T16 ) and R T12 , R T13 , R T14 , R T15 and R T16 each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group. Tm1, Tm2, ​​Tn1, and Tn2 each independently represent an integer of 0 or more and 2 or less. Examples of the substituent for each of the above groups include a halogen atom, an alkyl group having from 1 to 5 carbon atoms, and an alkoxy group having from 1 to 5 carbon atoms. Examples of the substituent for each of the above groups also include a substituted amino group substituted with an alkyl group having from 1 to 3 carbon atoms.

[0157] Here, among the triarylamine derivatives represented by the structural formula (a-1) and the benzidine derivatives represented by the structural formula (a-2), in particular, 6 H 4 -CH=CH-CH=C(R T7 )(R T8 )" and triarylamine derivatives having "-CH=CH-CH =C(R T15 )(R T16 ) is preferable from the viewpoint of charge mobility.

[0158] As the polymer charge transport material, known materials having charge transport properties such as poly-N-vinylcarbazole and polysilane are used. In particular, polyester-based polymer charge transport materials are particularly preferred. The polymer charge transport material may be used alone or in combination with a binder resin.

[0159] Examples of the binder resin used in the charge transport layer include polycarbonate resin, polyester resin, polyarylate resin, methacrylic resin, acrylic resin, polyvinyl chloride resin, polyvinylidene chloride resin, polystyrene resin, polyvinyl acetate resin, styrene-butadiene copolymer, vinylidene chloride-acrylonitrile copolymer, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinyl acetate-maleic anhydride copolymer, silicone resin, silicone alkyd resin, phenol-formaldehyde resin, styrene-alkyd resin, poly-N-vinylcarbazole, polysilane, etc. Among these, polycarbonate resin or polyarylate resin is suitable as the binder resin. These binder resins are used alone or in combination of two or more. The compounding ratio of the charge transport material to the binder resin is preferably from 10:1 to 1:5 by mass.

[0160] The charge transport layer may contain other well-known additives.

[0161] The formation of the charge transport layer is not particularly limited, and a known formation method can be used. For example, the charge transport layer can be formed by forming a coating film of a coating liquid for forming the charge transport layer in which the above components are added to a solvent, drying the coating film, and heating it as necessary.

[0162] Examples of solvents for preparing the coating liquid for forming the charge transport layer include ordinary organic solvents such as aromatic hydrocarbons such as benzene, toluene, xylene, and chlorobenzene, ketones such as acetone and 2-butanone, halogenated aliphatic hydrocarbons such as methylene chloride, chloroform, and ethylene chloride, and cyclic or linear ethers such as tetrahydrofuran and ethyl ether. These solvents may be used alone or in combination of two or more.

[0163] Examples of a coating method for coating the coating liquid for forming the charge transport layer on the charge generating layer include ordinary methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating and curtain coating.

[0164] The thickness of the charge transport layer is set, for example, preferably in the range of 5 μm or more and 50 μm or less, and more preferably in the range of 10 μm or more and 30 μm or less.

[0165] (protective layer) A protective layer is provided on the photosensitive layer as necessary for the purpose of, for example, preventing chemical changes in the photosensitive layer when the photosensitive layer is charged and further improving the mechanical strength of the photosensitive layer. Therefore, it is preferable to apply a layer composed of a cured film (crosslinked film) as the protective layer. Examples of such a layer include the following layers 1) and 2).

[0166] 1) A layer composed of a cured film of a composition containing a reactive group-containing charge transport material having a reactive group and a charge transport skeleton in the same molecule (i.e., a layer containing a polymer or crosslinked product of the reactive group-containing charge transport material). 2) A layer composed of a cured film of a composition containing a non-reactive charge transport material and a reactive group-containing non-charge transport material having no charge transport skeleton and having a reactive group (i.e., a non-reactive charge A layer comprising a charge transport material and a polymer or crosslinked product of the reactive group-containing non-charge transport material.

[0167] The reactive group of the reactive group-containing charge transport material may be a chain polymerizable group, an epoxy group, -OH, -OR (wherein R is an alkyl group), -NH 2 , -SH, -COOH, -SiR Q1 3-Qn (OR Q2 ) Qn [However, R Q1 represents a hydrogen atom, an alkyl group, or a substituted or unsubstituted aryl group; R Q2 represents a hydrogen atom, an alkyl group, or a trialkylsilyl group; Qn represents an integer of 1 to 3.

[0168] The chain polymerizable group is not particularly limited as long as it is a functional group capable of radical polymerization, and is, for example, a functional group having a group containing at least a carbon double bond.Specific examples include a group containing at least one selected from a vinyl group, a vinyl ether group, a vinyl thioether group, a styryl group (vinyl phenyl group), an acryloyl group, a methacryloyl group, and derivatives thereof.Among them, the chain polymerizable group is preferably a group containing at least one selected from a vinyl group, a styryl group (vinyl phenyl group), an acryloyl group, a methacryloyl group, and derivatives thereof, because of its excellent reactivity.

[0169] The charge transporting skeleton of the reactive group-containing charge transporting material is not particularly limited as long as it is a known structure in electrophotographic photoreceptors, and examples thereof include a skeleton derived from a nitrogen-containing hole transporting compound such as a triarylamine compound, a benzidine compound, a hydrazone compound, etc., and a structure conjugated with a nitrogen atom. Among these, a triarylamine skeleton is preferred.

[0170] The reactive group-containing charge transport material having a reactive group and a charge transporting skeleton, the non-reactive charge transport material, and the reactive group-containing non-charge transport material may be selected from well-known materials.

[0171] The protective layer may contain other well-known additives.

[0172] The formation of the protective layer is not particularly limited, and a well-known formation method can be used. For example, the protective layer can be formed by forming a coating film of a coating liquid for forming the protective layer in which the above components are added to a solvent, drying the coating film, and, if necessary, subjecting it to a curing treatment such as heating.

[0173] Examples of solvents for preparing a coating solution for forming a protective layer include aromatic solvents such as toluene and xylene, ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone, ester solvents such as ethyl acetate and butyl acetate, ether solvents such as tetrahydrofuran and dioxane, cellosolve solvents such as ethylene glycol monomethyl ether, and alcohol solvents such as isopropyl alcohol and butanol. These solvents may be used alone or in combination of two or more. The protective layer-forming coating liquid may be a solvent-free coating liquid.

[0174] Examples of a method for applying the protective layer-forming coating liquid onto a photosensitive layer (e.g., a charge transport layer) include conventional methods such as dip coating, push-up coating, wire bar coating, spray coating, blade coating, knife coating, and curtain coating.

[0175] The thickness of the protective layer is set, for example, preferably in the range of 1 μm or more and 20 μm or less, and more preferably in the range of 2 μm or more and 10 μm or less.

[0176] [Single-layer photosensitive layer] The single-layer type photosensitive layer (charge generating / transporting layer) is, for example, a layer containing a charge generating material, a charge transporting material, and, if necessary, a binder resin and other well-known additives. The materials are similar to those described for the charge generating layer and the charge transport layer. The content of the charge generating material in the single-layer photosensitive layer is preferably 0.1% by mass to 10% by mass, more preferably 0.8% by mass to 5% by mass, based on the total solid content. The content of the charge transport material in the single-layer photosensitive layer is preferably 5% by mass to 50% by mass, based on the total solid content. The method for forming the single-layer type photosensitive layer is the same as the method for forming the charge generating layer and the charge transport layer. The thickness of the single-layer photosensitive layer is, for example, 5 μm or more and 50 μm or less, and preferably 10 μm or more and 40 μm or less.

[0177] [Image forming devices, process cartridges] The image forming apparatus according to the present embodiment includes an electrophotographic photoreceptor, a charging device for charging the surface of the electrophotographic photoreceptor, an electrostatic latent image forming device for forming an electrostatic latent image on the surface of the charged electrophotographic photoreceptor, a developing device for developing the electrostatic latent image formed on the surface of the electrophotographic photoreceptor with a developer containing toner to form a toner image, and a transfer device for transferring the toner image to the surface of a recording medium. The electrophotographic photoreceptor according to the present embodiment is applied as the electrophotographic photoreceptor.

[0178] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as an apparatus provided with a fixing device that fixes a toner image transferred onto the surface of a recording medium; an apparatus of a direct transfer type that directly transfers a toner image formed on the surface of an electrophotographic photosensitive member onto a recording medium; an apparatus of an intermediate transfer type that performs primary transfer of a toner image formed on the surface of an electrophotographic photosensitive member onto the surface of an intermediate transfer member and secondary transfer of the toner image transferred onto the surface of the intermediate transfer member onto the surface of a recording medium; an apparatus provided with a cleaning device that cleans the surface of an electrophotographic photosensitive member before charging after the transfer of a toner image; an apparatus provided with a static elimination device that irradiates the surface of an electrophotographic photosensitive member with static elimination light to eliminate static electricity before charging after the transfer of a toner image; and an apparatus provided with an electrophotographic photosensitive member heating member for increasing the temperature of the electrophotographic photosensitive member and reducing the relative temperature.

[0179] In the case of an intermediate transfer type device, the transfer device is configured to have, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer device which primarily transfers the toner image formed on the surface of an electrophotographic photosensitive body onto the surface of the intermediate transfer body, and a secondary transfer device which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.

[0180] The image forming apparatus according to the present embodiment may be either a dry development type image forming apparatus or a wet development type image forming apparatus (a development type using a liquid developer).

[0181] In the image forming apparatus according to the present embodiment, for example, a portion including an electrophotographic photosensitive member may be a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including an electrophotographic photosensitive member according to the present embodiment is preferably used. In addition to the electrophotographic photosensitive member, the process cartridge may include at least one selected from the group consisting of a charging device, an electrostatic latent image forming device, a developing device, and a transfer device.

[0182] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this. Note that only the main parts shown in the drawings will be described, and descriptions of the rest will be omitted.

[0183] FIG. 2 is a schematic diagram showing an example of the image forming apparatus according to the present embodiment. As shown in Fig. 2, the image forming apparatus 100 according to this embodiment includes a process cartridge 300 having an electrophotographic photosensitive member 7, an exposure device 9 (an example of an electrostatic latent image forming device), a transfer device 40 (primary transfer device), and an intermediate transfer member 50. In the image forming apparatus 100, the exposure device 9 is disposed at a position where it can expose the electrophotographic photosensitive member 7 from the opening of the process cartridge 300, and the transfer device 40 is exposed to the electrophotographic photosensitive member 7 via the intermediate transfer member 50. The intermediate transfer body 50 is disposed at a position facing the electrophotographic photosensitive body 7, and a portion of the intermediate transfer body 50 is disposed in contact with the electrophotographic photosensitive body 7. Although not shown, the intermediate transfer body 50 also has a secondary transfer device that transfers the toner image transferred to the intermediate transfer body 50 onto a recording medium (e.g., paper). The intermediate transfer body 50, transfer device 40 (primary transfer device), and secondary transfer device (not shown) correspond to an example of a transfer device.

[0184] 2 supports an electrophotographic photoreceptor 7, a charging device 8 (an example of a charging device), a developing device 11 (an example of a developing device), and a cleaning device 13 (an example of a cleaning device) integrally within a housing. The cleaning device 13 has a cleaning blade (an example of a cleaning member) 131, which is disposed so as to come into contact with the surface of the electrophotographic photoreceptor 7. The cleaning member may not be in the form of the cleaning blade 131, but may be a conductive or insulating fibrous member, which may be used alone or in combination with the cleaning blade 131.

[0185] FIG. 2 shows an example of an image forming apparatus equipped with a fibrous member 132 (roll-shaped) that supplies lubricant 14 to the surface of the electrophotographic photosensitive member 7, and a fibrous member 133 (flat brush-shaped) that assists in cleaning, but these may be arranged as needed.

[0186] Hereinafter, each configuration of the image forming apparatus according to this embodiment will be described.

[0187] -Charging device- As the charging device 8, for example, a contact type charger using a conductive or semiconductive charging roller, charging brush, charging film, charging rubber blade, charging tube, etc. Also, a non-contact type roller charger, a scorotron charger or corotron charger that utilizes corona discharge, or other chargers known per se, can be used.

[0188] -Exposure equipment- The exposure device 9 may be, for example, an optical device that exposes the surface of the electrophotographic photoreceptor 7 with light such as semiconductor laser light, LED light, or liquid crystal shutter light in a predetermined image. The wavelength of the light source is within the spectral sensitivity range of the electrophotographic photoreceptor. The wavelength of the semiconductor laser is mainly near infrared light having an oscillation wavelength of about 780 nm. However, it is not limited to this wavelength, and a laser having an oscillation wavelength of 600 nm or a blue laser having an oscillation wavelength of 400 nm to 450 nm may also be used. In addition, a surface-emitting laser light source capable of outputting multiple beams is also effective for forming a color image.

[0189] -Developing device- The developing device 11 may be, for example, a general developing device that develops by contacting or non-contacting a developer. The developing device 11 is not particularly limited as long as it has the above-mentioned functions, and may be selected according to the purpose. For example, it may be a known developing device that has a function of attaching a one-component developer or a two-component developer to the electrophotographic photoreceptor 7 using a brush, roller, or the like. Among them, it is preferable to use a developing roller that holds a developer on its surface.

[0190] The developer used in the developing device 11 may be a one-component developer containing only toner, or may be a two-component developer containing toner and a carrier. The developer may be magnetic or non-magnetic. Well-known developers are used.

[0191] -Cleaning device- The cleaning device 13 is a cleaning blade type device equipped with a cleaning blade 131 . In addition to the cleaning blade system, a fur brush cleaning system or a simultaneous development and cleaning system may also be used.

[0192] -Transfer device- Examples of the transfer device 40 include known transfer chargers such as a contact type transfer charger using a belt, roller, film, rubber blade, etc., and a scorotron transfer charger or corotron transfer charger that utilizes corona discharge.

[0193] -Intermediate transfer body- A belt-like intermediate transfer belt containing semiconductive polyimide, polyamideimide, polycarbonate, polyarylate, polyester, rubber, etc. is used as the intermediate transfer body 50. The intermediate transfer body may be in the form of a drum other than a belt.

[0194] FIG. 3 is a schematic diagram showing another example of the image forming apparatus according to the present embodiment. 3 is a tandem-type multi-color image forming apparatus equipped with four process cartridges 300. In the image forming apparatus 120, the four process cartridges 300 are arranged in parallel on the intermediate transfer body 50, and one electrophotographic photosensitive body is used for each color. The image forming apparatus 120 has the same configuration as the image forming apparatus 100, except that it is a tandem type. EXAMPLES

[0195] The electrophotographic photoreceptor of the present disclosure will be described in more detail below with reference to examples. The materials, amounts, ratios, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present disclosure. Therefore, the scope of the electrophotographic photoreceptor of the present disclosure should not be interpreted as being limited by the specific examples shown below.

[0196] -Preparation of electron transport material- (Preparation of Electron Transporting Material (1)) 6.4 parts by mass of an exemplary compound (P-1: referred to as "P-1α" in the table) which is an electron transport material represented by the general formula (P) and has an α crystal type (CCDC196996: K. Tojo, J. Mizuguchi CCDC 196996: Experimental Crystal Structure Determination, 2002, DOI: DOI: 10. 5517 / cc6lzrg), 72 parts by mass of zirconia beads with a diameter of 0.3 mm, and 1.0 part by mass of sodium chloride were placed in a zirconia container and ground at a rotation speed of 500 rpm for 2 hours using a planetary mill (Fritsch: P-7 Classic Line). After grinding, the particles were separated by filtration while washing the zirconia beads with 500 ml of distilled water. The resulting aqueous dispersion of particles was centrifuged, and the supernatant water was removed by decantation to isolate the electron transport material. The isolated electron transport material was repeatedly washed with water until the electrical conductivity was 10 μS / cm or less, and then dried in a freeze dryer for 48 hours to obtain an electron transport material (1) having the aspect ratio and average primary particle size shown in Table 1.

[0197] (Preparation of Electron Transporting Material (2)) In the preparation of electron transport material (1), the material used was changed from the exemplary compound (P-1) having an α crystal type to an exemplary compound (P-1: referred to as "P-1β" in the table) having a β crystal type ((CCDC196997, K. Tojo, J. Mizuguchi CCDC 196997: Experimental Crystal Structure Determination, 2002)), and an electron transport material (2) was obtained by the same procedure.

[0198] (Preparation of Electron Transporting Material (3)) The electron transport material (3) was obtained in the same manner as in the preparation of the electron transport material (1), except that the material used was changed to the exemplified compound (Q-12) having a crystal type [CCDC798609: MUSchmidt, EFPaulus, N.Rademacher, GMDay CCDC 798609: Experimental Crystal Structure Determination, 2010].

[0199] (Preparation of Electron Transporting Material (4)) In the preparation of electron transport material (1), the grinding process using a planetary mill and the subsequent process of filtering and isolating the particles after grinding were omitted. Instead, the material was repeatedly washed with water until the electrical conductivity reached 10 μS / cm or less, and then dried in a freeze dryer for 48 hours. The same procedure was followed to prepare electron transport material (4).

[0200] (Preparation of Electron Transporting Material (C1)) In the preparation of the electron transporting material (1), the material used was changed to the following compound (D) having the crystal structure [COD8100240: Mizuguchi, Jin Crystal structure of trans-bisbenzimidazo[2,1-b:1',2'-j]benzo[lmn] [3,8]-phenanthroline-6,9-dione, C~26~H~12~N~4~O~2~Zeitschrift fur Kristallographie - New Crystal Structures, 2003, 218, 137-138]. The same procedure was followed to prepare the electron transporting material (C1).

[0201] [ka]

[0202] (Preparation of Electron Transporting Material (C2)) Electron transport material (C2) was obtained by the same procedure as in the preparation of electron transport material (1), except that the material used was changed to the following compound (E), which has the crystal structure [DA Zherebtsov, MU Schmidt, R. Niewa, CP Sakthidharan, FV Podgornov, YV Matveychuk, SA Nayfert, MA Polozov, SN Ivashevskaya, AI Stash, Y.-S. Chen, DE Zhivulin, VE Zhivulin, SV Merzlov, EV Bartashevich, VV Avdin, HS Hsu, FW Guo CCDC 1872270: Experimental Crystal Structure Determination, 2019].

[0203] [ka]

[0204] (Preparation of Electron Transporting Material (C3)) An electron transporting material (C3) was obtained in the same manner as in the preparation of the electron transporting material (4), except that the material used was changed to the above-mentioned compound (D) having the crystal structure of COD8100240.

[0205] - Preparation of undercoat layer - (Preparation of Undercoat Layer (1)) A mixed solution was obtained by mixing 60 parts of the electron transport material (1), 13.5 parts of a curing agent (blocked isocyanate Sumidur 3175, manufactured by Sumitomo Bayern Urethane Co., Ltd.), 15 parts of a butyral resin (S-LEC BM-1, manufactured by Sekisui Chemical Co., Ltd.), and 85 parts of methyl ethyl ketone. 38 parts of this mixed solution and 25 parts of methyl ethyl ketone were mixed, and dispersed for 3 hours in a sand mill using 1 mmφ glass beads to obtain a dispersion solution. To the resulting dispersion, 0.005 parts of dioctyltin dilaurate was added as a catalyst to obtain a coating solution for the undercoat layer. This coating solution was applied onto a cylindrical aluminum substrate by dip coating, and dried and cured at 170°C for 30 minutes to obtain a 10 μm thick undercoat layer.

[0206] (Preparation of Undercoat Layer (2)) An undercoat layer (2) was obtained in the same manner as for the undercoat layer (1), except that the electron transporting material in the undercoat layer (1) was changed to an electron transporting material (2).

[0207] (Preparation of Undercoat Layer (3)) An undercoat layer (3) was obtained in the same manner as for the undercoat layer (1), except that the electron transporting material in the undercoat layer (1) was changed to an electron transporting material (3).

[0208] (Preparation of Undercoat Layer (4)) An undercoat layer (4) was obtained in the same manner as in the preparation of the undercoat layer (1), except that the step of dispersing with a sand mill in the preparation of the undercoat layer (1) was changed to a step of dispersing with a paint shaker for 2 hours.

[0209] (Preparation of Undercoat Layer (5)) An undercoat layer (5) was obtained in the same manner as in the undercoat layer (4), except that the electron transporting material (1) was changed to the electron transporting material (2).

[0210] (Preparation of Undercoat Layer (6)) An undercoat layer (6) was obtained in the same manner as in the undercoat layer (4), except that the electron transporting material (1) was changed to the electron transporting material (3).

[0211] (Preparation of Undercoat Layer (7)) An undercoat layer (7) was obtained in the same manner as in the undercoat layer (4), except that the electron transporting material (1) in the undercoat layer (4) was changed to the electron transporting material (4).

[0212] (Preparation of Undercoat Layers (8) to (9)) Subcoat layers (8) to (9) were obtained in the same manner, except that the content of the electron transport material (1) in the subcoat layer (1) was changed to the content shown in the table relative to the total solid content of the subcoat layer.

[0213] (Preparation of Undercoat Layers (10) to (11)) Subcoat layers (10) to (11) were obtained in the same manner as for the subcoat layer (1), except that the thickness of the subcoat layer was changed to the thickness shown in the table.

[0214] (Preparation of Undercoat Layer (12)) An undercoat layer (12) was obtained in the same manner as in the undercoat layer (1), except that the proportion of the metal oxide was changed to 10 mass %.

[0215] (Preparation of Comparative Sublayer (1)) A comparative subcoat layer (1) was obtained in the same manner as in the subcoat layer (1), except that the electron transporting material (1) was changed to the electron transporting material (C1).

[0216] (Preparation of Comparative Sublayer (2)) A comparative subcoat layer (2) was obtained in the same manner as in the subcoat layer (1), except that the electron transporting material (1) was changed to the electron transporting material (C2).

[0217] (Preparation of Comparative Sublayer (3)) A comparative subcoat layer (3) was obtained in the same manner as in the subcoat layer (1), except that the electron transporting material (1) was changed to the electron transporting material (C3).

[0218] Table 1 shows the crystal density, FWHM, LUMO energy level and maximum value Nmax, as well as the aspect ratio and average primary particle size of the electron transport material in the undercoat layer, which were measured by the above-mentioned measuring methods. In Table 1, the crystal density of the electron transporting material in the undercoat layer is referred to as "crystal density." In Table 1, the full width at half maximum of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer is referred to as "FWHM." In Table 1, "maximum value Nmax" refers to the relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer. 1 The relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured by powdering the undercoat layer with a volume average particle size of 5 μm or less was defined as I 2 When N is the orientation index, N is the maximum value Nmax of the orientation index N expressed by the above-mentioned formula (1). In Table 1, "LUMO" refers to the LUMO energy level of the undercoat layer. In Table 1, the "content" in the "electron transporting material" column refers to the content of the electron transporting material relative to the total solid content of the undercoat layer. In Table 1, "proportion of metal oxide" refers to the proportion of metal oxide to the total solid content of the undercoat layer.

[0219] <Examples 1 to 12 and Comparative Examples 1 to 3> (Formation of Charge Generation Layer) A mixture of 15 parts by mass of hydroxygallium phthalocyanine, which has diffraction peaks at Bragg angles (2θ±0.2°) of at least 7.3°, 16.0°, 24.9°, and 28.0° in the X-ray diffraction spectrum using Cukα characteristic X-rays, 10 parts by mass of vinyl chloride-vinyl acetate copolymer resin (VMCH, manufactured by Nippon Unicar Co., Ltd.) as a binder resin, and 200 parts by mass of n-butyl acetate was stirred and dispersed in a sand mill using glass beads with a diameter of 1 mm for 4 hours. 175 parts by mass of n-butyl acetate and 180 parts by mass of methyl ethyl ketone were added to the obtained dispersion and stirred to obtain a coating liquid for forming a charge generation layer. This coating liquid for forming a charge generation layer was dip-coated on the outer surface of the undercoat layer of the type shown in the table, and dried at 150° C. for 15 minutes to form a charge generation layer with a thickness of 0.2 μm.

[0220] (Formation of charge transport layer) 38 parts by mass of the following charge transport material (HT-1), 10 parts by mass of the following charge transport material (HT-2), 52 parts by mass of the following polycarbonate resin (A) (viscosity average molecular weight: 46,000), and 0.3 parts by mass of a fluorine-containing graft polymer (manufactured by Toa Gosei: GF-500) as a dispersing aid were added and dissolved in 800 parts by mass of tetrahydrofuran, and 8 parts by mass of tetrafluoroethylene resin (manufactured by Daikin Industries: Lubron L5, average particle size 300 nm) were added, and the mixture was dispersed for 2 hours at 5500 rpm using a homogenizer (manufactured by IKA: Ultra Turrax) to obtain a coating liquid for forming a charge transport layer. This coating liquid was applied onto the charge generation layer, and dried at 140° C. for 40 minutes to form a charge transport layer with a film thickness of 30 μm. This was used as an electrophotographic photoreceptor.

[0221] [ka]

[0222] [ka]

[0223] <Evaluation> The electrophotographic photoreceptor of each of the Examples and Comparative Examples was mounted on a modified image forming apparatus DocuCentre C5570 manufactured by FUJIFILM Business Innovation Co., Ltd., and the following evaluations were carried out. The results of each evaluation are shown in Table 1.

[0224] -Evaluation of charge retention- In an environment with a temperature of 20°C and a relative humidity of 40%, the photoconductor was charged by a scorotron charger with a grid voltage of -800V, and 1 million images were output without exposure. After that, the photoconductor was charged again by a scorotron charger with an applied voltage of -800V, and the potential was measured 200msec later. The potential of the photoconductor was determined by subtracting the potential 150msec later from the measured potential when initially charged at -800V (amount of potential drop), and this was used as an index of chargeability. A: The measured potential is less than -15V. B: The measured potential was -15V or more and less than -18V. C: The measured potential was -18V or more and less than -20V. D: The measured potential was greater than -20V and less than -22V. E: The measured potential was -22V or higher.

[0225] -Evaluation of electron transport performance- In an environment with a temperature of 20°C and a relative humidity of 40%, the photoconductor was charged with a scorotron charger with a grid voltage of -700V, and a 780nm semiconductor laser was used to measure 4.0 erg / cm 2 After irradiation with light, the potential was measured at a position corresponding to 70 msec after charging.

[0226] A: The potential after exposure was less than -50V. B: The potential after exposure was −50V or more and less than −57V. C: The potential after exposure was −57 or more and less than −60. D: The potential after exposure was −60 or more and less than −65. E: The potential after exposure was −65 or higher.

[0227] [Table 1]

[0228] As shown in Table 1, it was found that the electrophotographic photoreceptors of the Examples were superior in electron transport properties to the electrophotographic photoreceptors of the Comparative Examples, and were also superior in charge retention to the electrophotographic photoreceptors of the Comparative Examples.

[0229] The present embodiment includes the following aspects. (((1))) A conductive substrate; an undercoat layer provided on the conductive substrate; a photosensitive layer provided on the undercoat layer; Equipped with The undercoat layer is made of a binder resin and a crystal density of 1.62 g / cm 3and wherein the full width at half maximum (FWHM) of the maximum intensity peak in an X-ray diffraction spectrum measured in the thickness direction is 5° or less. (((2))) The electrophotographic photoreceptor according to (((1))) above, wherein the electron transporting material has an aspect ratio of 1.0 or more and 2.5 or less. (((3))) The electrophotographic photoreceptor according to (((2))) above, wherein the electron transporting material has an aspect ratio of 1.5 or more and 2.3 or less. (((4))) The relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the subbing layer is I 1 year, The above undercoat layer is powdered with a volume average particle size of 5 μm or less and the relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum is measured. 2 The electrophotographic photoreceptor according to (((1))) above, wherein, when the orientation index N is expressed by the following formula (1), a maximum value Nmax is 1.0 or more and 5.5 or less:

number

[0230] According to the invention related to (((1))), when the full width at half maximum (FWHM) of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer containing a binder resin and an electron transporting material exceeds 5.0°, or when the crystal density of the electron transporting material is 1.62 g / cm 3 In comparison with the case where the content is less than 100%, an electrophotographic photoreceptor having excellent electron transport properties is provided. According to the invention related to (((2))), an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case where the aspect ratio of the electron transport material exceeds 2.5. According to the invention related to (((3))), an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with the case where the aspect ratio of the electron transport material is less than 1.5 or exceeds 2.3. According to the invention related to (((4))), the relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer is I 1 The relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured by powdering the undercoat layer with a volume average particle size of 5 μm or less was defined as I 2 In this case, an electrophotographic photoreceptor having excellent electron transport properties can be provided, as compared with a case in which the maximum value Nmax of the orientation index N represented by the formula (1) is 1.0 or more and exceeds 5.5. According to the invention related to (((5))), an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case in which the LUMO energy level of the undercoat layer is less than 3.8 eV or more than 4.2 eV.

[0231] According to the invention related to (((6))), (((7))) or (((8))), an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case in which the electron transport material contains the following compound (D) or compound (E). [ka]

[0232] According to the invention related to (((9))), an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case in which the average primary particle diameter of the electron transporting material exceeds 500 nm. According to the invention related to (((10))), an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case in which the content of the electron transport material is less than 60 mass % or more than 75 mass % relative to the total solids content of the undercoat layer. According to the invention related to (((11))), an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with cases in which the thickness of the undercoat layer is less than 5 μm or exceeds 15 μm. According to the invention related to (((12))), an electrophotographic photoreceptor having excellent electron transport properties is provided, as compared with a case in which the proportion of the metal oxide in the undercoat layer exceeds 5 mass % with respect to the total solid content of the undercoat layer. According to the invention related to (((13))) or (((14))), an electrophotographic photoreceptor is provided in which the full width at half maximum (FWHM) of the maximum intensity peak in an X-ray diffraction spectrum measured in the thickness direction of an undercoat layer containing a binder resin and an electron transporting material exceeds 5.0°, or the crystal density of the electron transporting material is 1.62 g / cm 3 In comparison with a process cartridge or image forming apparatus having an electrophotographic photosensitive member with an excellent electron transporting property, a process cartridge or image forming apparatus having an electrophotographic photosensitive member with an excellent electron transporting property is provided. [Explanation of symbols]

[0233] 1 undercoat layer, 2 charge generation layer, 3 charge transport layer, 4 conductive substrate, 5 photosensitive layer, 7A electrophotographic photosensitive member, 7 electrophotographic photosensitive member, 8 charging device, 9 exposure device, 11 developing device, 13 cleaning device, 14 lubricant, 40 transfer device, 50 intermediate transfer body, 100 image forming apparatus, 120 image forming apparatus, 131 cleaning blade, 132 fibrous member (roll-shaped), 133 fibrous member (flat brush-shaped), 300 process cartridge

Claims

1. A conductive substrate; an undercoat layer provided on the conductive substrate; a photosensitive layer provided on the undercoat layer; Equipped with The undercoat layer is made of a binder resin and a crystal density of 1.62 g / cm 3 and wherein the full width at half maximum (FWHM) of the maximum intensity peak in an X-ray diffraction spectrum measured in the thickness direction is 5.0° or less.

2. The electrophotographic photoreceptor according to claim 1 , wherein the electron transporting material has an aspect ratio of 1.0 or more and 2.5 or less.

3. The electrophotographic photoreceptor according to claim 2 , wherein the electron transporting material has an aspect ratio of 1.5 or more and 2.3 or less.

4. The relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum measured in the thickness direction of the undercoat layer is expressed as I 1 year, The above undercoat layer is in a powder state with a volume average particle size of 5 μm or less, and the relative integrated intensity of the maximum intensity peak in the X-ray diffraction spectrum is measured. 2 2. The electrophotographic photoreceptor according to claim 1, wherein, when the orientation index N is expressed by the following formula (1), a maximum value Nmax is 1.0 or more and 5.5 or less: [0010]

5. 2. The electrophotographic photoreceptor according to claim 1, wherein the LUMO energy level of the undercoat layer is from 3.8 eV to 4.2 eV.

6. 2. The electrophotographic photoreceptor according to claim 1, wherein the electron transporting material contains at least one of an electron transporting material represented by the following general formula (P) and an electron transporting material represented by the following general formula (Q): 【Chemistry 1】 In the above general formula (P), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, an aralkyl group, an aryl group, an alkoxycarbonyl group, or a halogen atom. In the above general formula (Q), R 51 and R 52 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, an aralkyl group, an aryl group, an alkoxycarbonyl group, or a halogen atom.

7. In the general formula (P), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 and R 8 The electrophotographic photoreceptor according to claim 6 , wherein each independently represents a hydrogen atom or a halogen atom.

8. In the general formula (Q), R 51 and R 52 The electrophotographic photoreceptor according to claim 6 , wherein represents a hydrogen atom.

9. 2. The electrophotographic photoreceptor according to claim 1, wherein the electron transporting material has an average primary particle size of 500 nm or less.

10. 2 . The electrophotographic photoreceptor according to claim 1 , wherein the content of the electron transporting material is from 60% by mass to 75% by mass based on the total binder resin content of the undercoat layer.

11. 2. The electrophotographic photoreceptor according to claim 1, wherein the undercoat layer has a thickness of 5 [mu]m or more and 15 [mu]m or less.

12. The electrophotographic photoreceptor according to claim 1 , wherein the ratio of the metal oxide in the undercoat layer is 5% by mass or less based on the total solid content of the undercoat layer.

13. The electrophotographic photoreceptor according to any one of claims 1 to 12 is provided, A process cartridge that is detachably attached to an image forming apparatus.

14. The electrophotographic photoreceptor according to any one of claims 1 to 12, a charging device for charging a surface of the electrophotographic photoreceptor; an electrostatic latent image forming device for forming an electrostatic latent image on the charged surface of the electrophotographic photoreceptor; The electrostatic latent image formed on the surface of the electrophotographic photoreceptor is developed with a developer containing a toner. a developing device for forming a toner image by using the toner; a transfer device for transferring the toner image onto a surface of a recording medium; An image forming apparatus comprising:

Citation Information

Patent Citations

  • Electrophotographic sensitive body

    JP1991216662A

  • Electrophotographic sensitive body

    JP1993249719A

  • Electrophotographic photoreceptor

    JP1999184129A

  • Electrophotographic photoreceptor

    JP1999202520A